The new separation of powers a theory for the modern state - Carolan, Eoin. (Oxford : Oxford University Press, 2009)
This book offers a radical & provocative revision of the theory of separation of powers. It argues that, although designed to protect democracy, separation of powers is often used today to undermine it by concealing & centralising the exercise of power by public officials. The theory is then reinvented for the modern regulatory state.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Separation of powers; Judicial independence; Separation of powers -- Great Britain -- Case studies; Separation of powers -- Ireland -- Case studies; Separation of powers -- United States -- Case studies